Virulence and Antibiotic Resistance Genes in Listeria monocytogenes Strains Isolated From Ready-to-Eat Foods in Chile - Parra-Flores, Julio; Holý, Ondrej; Bustamante, Fernanda; Lepuschitz, Sarah; Pietzka, Ariane; Contreras-Fernández, Alejandra; Castillo, Claudia; Ovalle, Catalina; Alarcón-Lavín, María Paula; Cruz-Córdova, Ariadnna; Xicohtencatl-Cortes, Juan; Mancilla-Rojano, Jetsi; et al. (Frontiers in Microbiology, 2022)
This study explored the virulence factors and antibiotic resistance in Listeria monocytogenes strains isolated from ready-to-eat (RTE) foods through in vitro and in silico testing by whole-genome sequencing (WGS). The L. monocytogenes was identified in RTE foods by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF) and WGS. Virulence genes detection were performed by polymerase chain reaction (PCR), and the antibiotic resistance profiles were determined by the disk diffusion method. Virulence and resistance genes, plasmids, and mobile genetic elements (MGEs) were identified using RidomSeqSphere+, PlasmidFinder, Comprehensive Antibiotic Resistance Database platform, and MGEfinder. The CRISPR-Cas system was determined using CRISPRCasFinder and CRISPRminer. The overall positivity of L. monocytogenes in the RTE food samples was 3.1% in 14 isolated strains. Listeria monocytogenes ST8, ST2763, ST1, ST3, ST5, ST7, ST9, ST14, ST193, and ST451 sequence types were identified by average nucleotide identity, ribosomal multilocus sequence typing (rMLST), and core genome MLST. Seven isolates had serotype 1/2a, five 1/2b, one 4b, and one 1/2c. All strains expressed the three virulence factors in vitro and three strains exhibited resistance to ampicillin. All isolates showed the bsh, clpCEP, hly, hpt, iap/cwhA, inlA, inlB, ipeA, lspA, mpl, plcA, pclB, oat, pdgA, and prfA genes. One isolate exhibited a type 11 premature stop codon (PMSC) inlA gene and another isolate a new mutation (deletion of A in position 819). All strains carried the fosX, lin, norB, mprF, tetA, and tetC resistance genes. In addition, the arsBC, bcrBC, and clpL genes were detected that conferred resistance to stress and disinfectants. The Inc18(rep25), Inc18(rep26), and N1011A plasmids and MGEs were found in nine isolates. Ten isolates showed CAS-Type II-B systems; in addition, Anti-CRISPR AcrIIA1 and AcrIIA3 phage-associated systems were detected in three genomes. The presence of virulence and antibiotic resistance genes in L. monocytogenes strains isolated from RTE foods poses a health problem for the consumer